Kualitas Media Pembelajaran Digital Mahasiswa PGSD - Dian Fitri Nur Aini; Kumalasani, Maharani Putri; Kusumaningtyas, Dian Ika (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2023)
The COVID-19 pandemic, which has persisted for two years, has significantly impacted various sectors, including learning-related education. However, along with the decline in COVID-19 cases, the government has provided recommendations and the freedom for learning to be carried out with limited face-to-face meetings. One of the essential learning tools to support online and offline learning is digital learning media. Teachers and prospective teachers can develop digital learning media with four aspects, namely content, learning design, learning media and communication, as well as implementation power and user response. The aim of this study is to provide an in-depth description of the quality of content aspects, learning design and the construct of digital learning media for PGSD (Primary School Teacher Education) students. This research employed a qualitative research design. The research model used in this study is a descriptive model describing the quality of digital learning media developed by PGSD students. It was conducted at the University of Muhammadiyah Malang and the University of Borneo. The subjects in this study were UMM PGSD and Borneo University PGSD students. The instruments used in this study were observation guidelines, questionnaires, assessment instruments and interviews. The average quality of the content aspect reached 86%, the learning design aspect reached 83%, and the construct aspect reached 85%, all three of which showed outstanding results. The existence of digital learning media that has excellent quality in the teaching and learning process will increase students' learning motivation.